Neurophysiology of the “Celiac Brain”: Disentangling Gut-Brain Connections - Pennisi, Manuela; Bramanti, Alessia; Cantone, Mariagiovanna; Pennisi, Giovanni; Bella, Rita; Lanza, Giuseppe (Frontiers in Neuroscience, 2017)
Celiac disease (CD) can be considered a complex multi-organ disorder with highly variable extra-intestinal, including neurological, involvement. Cerebellar ataxia, peripheral neuropathy, seizures, headache, cognitive impairment, and neuropsychiatric diseases are complications frequently reported. These manifestations may be present at the onset of the typical disease or become clinically evident during its course. However, CD subjects with subclinical neurological involvement have also been described, as well as patients with clear central and/or peripheral nervous system and intestinal histopathological disease features in the absence of typical CD manifestations. Based on these considerations, a sensitive and specific diagnostic method that is able to detect early disease process, progression, and complications is desirable. In this context, neurophysiological techniques play a crucial role in the non-invasive assessment of central nervous system excitability and conductivity. Moreover, some of these tools are known for their valuable role in early diagnosis and follow-up of several neurological diseases or systemic disorders such as CD with nervous system involvement, even at the subclinical level. This review provides an up-to-date summary of the neurophysiological basis of CD using electroencephalography, multimodal evoked potentials, and transcranial magnetic stimulation. The evidence examined here seems to converge on an overall profile of “hyperexcitable celiac brain”, which partially recovers after institution of a gluten-free diet. The main translational correlate is that in case of subclinical neurological involvement or overt unexplained symptoms, neurophysiology could contribute to the diagnosis, assessment, and monitoring of a potentially underlying CD.